RECLAIMING ISLAMIC SCIENTIFIC LEGACY: ADDRESSING THE KNOWLEDGE CRISIS IN THE MUSLIM WORLD (Al-Aasar, 2025)
Allah Almighty, by linking the concepts of religion, humanity, welfare, and success with the pursuit of knowledge, bestowed not only the understanding of material objects but also divine guidance upon Hazrat Adam (peace be upon him). The first revelation to Prophet Muhammad (peace be upon him), consisting of five verses, also began with the command to read and invoked the name of the Almighty, emphasizing that Islam is rooted in knowledge and wisdom rather than superstition or conjecture. From this perspective, Islam established the foundation of human life, society, economy, and politics on the principles of certainty, divine revelation, and beneficial knowledge, in contrast to the mythologies and distortions found in earlier religious traditions. Despite these foundational principles, Muslim countries, which should have led the world in scientific research and innovation based on the teachings of Islam, now rank among the lowest in scientific progress and technological advancements. The same civilization that once contributed significantly to scientific discoveries—producing a thousand groundbreaking inventions that influenced global knowledge—now lags behind, failing to keep pace with contemporary scientific and technological advancements. In this context, Pakistan, which should have been a leader in science and research within the Muslim world, is experiencing continuous decline instead of progress. Given these circumstances, it is imperative to critically analyze the role of the Muslim Ummah, particularly the State of Pakistan, in addressing this intellectual and developmental crisis. A thoughtful approach and the implementation of effective, practical measures are essential to reclaiming the lost legacy of scientific and technological leadership.